Unilateral branch retinal vein occlusion and contralateral branch retinal artery occlusion: a case report and comprehensive literature review - Chao Zhang; Han Wang; Zhiyu Xu; Qiwei Lu; Ying Zhu; Jun Li (Frontiers in Medicine)
Branch retinal vein occlusion (BRVO) and branch retinal artery occlusion (BRAO) are two distinct yet serious retinal vascular disorders that often present with acute visual impairment. While both conditions are commonly encountered independently, their simultaneous or sequential occurrence in opposite eyes of the same patient is exceedingly rare and poses unique diagnostic and therapeutic challenges. Here, we present the case of a 65-year-old male patient with a history of systemic hypertension who developed BRAO in the right eye and BRVO in the left eye within a short time interval. Detailed ophthalmologic examination, multimodal imaging including optical coherence tomography (OCT) and fundus fluorescein angiography (FFA), and systemic vascular assessments such as carotid Doppler ultrasonography and cardiac evaluation were performed to identify the underlying etiology and guide treatment decisions. The patient was found to have significant carotid atherosclerosis with plaque formation, suggesting systemic vascular pathology as a shared risk factor for both events. Ocular treatment involved posterior sub-Tenon injection of corticosteroids, vasodilator therapy, and laser photocoagulation for ischemic areas. Visual acuity showed marked improvement in both eyes after appropriate interventions and systemic blood pressure control. The concurrent presentation of BRVO and BRAO in different eyes may reflect a systemic vascular disease burden and warrants a high index of suspicion for underlying cardiovascular or cerebrovascular abnormalities. This case underscores the importance of prompt ocular diagnosis, thorough systemic evaluation, and multidisciplinary collaboration to prevent further vascular events and preserve visual function. A detailed literature review is also provided to contextualize the clinical features, diagnostic tools, management approaches, and prognosis of such rare bilateral retinal vascular presentations.